Fumigant Toxicity and Repellent Effect of Seed Essential Oil of Celery Against Lesser Grain Borer, Rhyzopertha dominica F. Issue 1 (2nd January 2018) - Ebadollahi, Asgar
Abstract: The lesser grain borer, Rhyzopertha dominica F., is one of the most serious stored-products insect pests throughout the world. Application of chemical pesticides for controlling such pests has caused many side-effects such as environmental pollution, toxicity to non-target organisms and human health threats. Accordingly, several studies have been conducted to utilize the lower risk substitutes in the recent years. In the present study, chemical components of the essential oil extracted from seeds of celery ( Apium graveolens L.) and its toxic and repellant effects were investigated on R. dominica . Chemical analysis of the essential oil by Gas Chromatography-Mass Spectrometry (GC-MS) resulted in the identification of 29 compounds, in which α- pinene (13.08%), β-pinene (10.37%), γ-3-carene (8.96%), myristicin (35.41%) and apiol (8.34%) had a high amount. Celery essential oil has a significant toxicity on the adults of R. dominica . The lethal concentration to kill 50% insect population (LC50 ) was estimated as 53.506 (48.131 - 59.670) μl/l after 24 h exposure time. This value decreased to 33.285 (29.636 - 37.137) μl/l with increasing the time to 72 hours. The overall mortality rate is directly related to increasing the essential oil concentrations and exposure times. Investigating the repellency of the sub-lethal concentrations of essential oil displayed that the highest repellent percentage (70 ± 3.54) was attained with a concentration of 47.764 μl/l at 6 h. Due to considerable toxicity and repellency against R. dominica, the essential oil of celery seeds may be pondered as a potential bio-rational agent for management of this pest.